Between Hope and Despair is Resolve: Remembering Roger Simon - Pinar, William (Journal of the Canadian Association for Curriculum Studies, 2014)
The traditional understanding of abstract does not apply in this case. This article is a memoir written in honour of the late Roger Simon. The work seeks to honour both Roger Simon and his body of work.